Kamisama kiss. Vol. 11 - Suzuki, Julietta (Viz Media, 2012)
Nanami Momozono is alone and homeless after her dad skips town to evade his gambling debts and the debt collectors kick her out of her apartment. So when a man she's just saved from a dog offers her his home, she jumps at the opportunity. But it turns out that his place is a shrine, and Nanami has unwittingly taken over his job as a local deity! New Year's is coming up, and that means the Mikage Shrine needs to send a representative to greet the toshigami, the visiting kami who assures a good harvest for the year. Nanami insists on going with her shinshi but gets stuck in limbo at the meeting place. Her shinshi rush to get her back, but instead they all end up trapped in Nanami's troubled childhood ...